Joint Responsibility at its Peak – Searching for a New Nordic Unemployment Model - Dahl, Tora (Nordic Journal of Working Life Studies, 2012)
Earlier research has shown that the Nordic Ghent systems seem to be weakened. The unemployment insurances administered by the unions have experienced a decline in numbers of members, very similar to the drop in trade union membership. This article takes its point of departure in previous research into the decline in the membership densities of unemployment insurances in several Nordic countries. The article examines these tendencies and focuses on a new and rather atypical example of organizing unemployment systems in a Nordic context, namely that of the Faroe Islands. Based on interviews and documentation analysis, the article describes the system extensively and argues conclusively that the Faroese unemployment insurance system is an example of the deeply rooted Nordic negotiation tradition, albeit in a new context in which the labor market parties stand united to ensure the system’s autonomy from political influence.